Aspectos prosódicos de duração e pausa de agrupamentos numéricos de telefone móvel: um enfoque na libras - Marques, Ewerton Carlos Matos (2020)
The numerical groupings in Brazilian Sign Language - Libras, like any other language, are made up of regular and fixed linguistic structures that integrate expressions whose meaning depends on maintaining the order of their constituents. Although we have, in Libras, some intuition about how its structural organization is established, there are no studies that investigate which prosodic characteristics are involved in this type of linguistic modality. Thus, this research aims to describe how cell numbers are structured by fluent deaf signers in Libras. The importance of this study refers to the contribution to a little explored area: the prosody of sign languages. The role of prosody in the interaction in sign languages is evidenced by Leite (2008) who segments the discourse through the presence of prosodic groupings. The prosody of numbers is emphasized by Almeida (2017) who describes the role of prosody in the composition of the structure of nominal numbers in Brazilian Portuguese and by Musiliyu (2014) who identified intonational patterns of numerical groupings associated with telephone numbers in Brazilian Portuguese. We then seek to observe the prosodic behavior in the realization of the groupings in Libras. The methodology used is organized in stages: (i) data collection through interview in Libras through spontaneous signaling and reading of numerical groupings projected through slides; (ii) segmentation and annotation of interviews at ELAN; (iii) transfer of the annotations made in ELAN, to a file with Praat textgrid extension (BOERSMA, 2001) to automate, through the Analyze tier script (HIRST, 2012), the duration values necessary for data analysis, identifying the duration and the pause indicators performed when signaling telephone numbers, as well as what characterizes them as prosodic groupings that define their structure. The results revealed that the preference of the Deaf in signaling cell numbers seems to be using a decimal organization in units and subdividing the grouping into binary or even ternary prosodic units. We did not identify a pattern of numerical frequency distribution, neither in the data read nor in the spontaneous data, since we did not identify statistically significant differences between the frequencies of numerical distribution presented by the research participants. We identified both in the reading data and in the personal data, the signaling of numbers located in a pre-border position with a significantly longer duration than the numbers that were not located in a border position, which indicates an elongation of the signal as a marking clue prosodic frontier. On the other hand, our findings reveal that the pause does not seem to be a relevant prosodic parameter to mark the boundary between prosodic units in signaling cellular numerical clusters. With regard to the duration of the numerical groupings as a whole, when comparing read and spontaneous data, we did not find any statistically significant differences between such duration values.